Type studies on frullania subgenus meteoriopsis. vi. subgeneric affiliation of selected asiatic species previously assigned to subg. meteoriopsis (2011)
A type revision of the types of Asiatic species previously assigned to Frullaniasubgenus. Meteoriopsis revealed that they were erroneously included in that subgenus. Evidence presented here shows that F. seriatifolia Steph., F. ternatensis Gottsche, F. trichodes Mitt. and F. vaginata (Sw.) Nees are members of F. subg. Thyopsiella, and F. grandiclava Steph. and F. orientalis Sande-Lac. of F. subg. Frullania sect. Orientalis.